Spray development and combustion simulation for simple injection chamber - Mohd Hafizuddin, Abdul Rahim (2013)
This thesis is related to the simulation results conducted to injectors and combustion chamber using a simple computational Fluid Dynamic. Injectors and combustion chamber design using SolidWorks 2012 and flow simulation software used is from SolidWorks Flow Simulation 2012. Simulation to be carried out based on the differential pressure injector to inject. While for simulated combustion chamber front, it is carried out based on the difference in pressure at the injectors and air/fuel ratio, the normal level of 13:1. Simulation of the combustion chamber is also carried out with four different strokes, the intake stroke, compression stroke, power stroke and exhaust stroke. It is possible to identify differences in contour in every stroke. Characteristics that need to be identified in this injector simulation are an area of wide angle spray and spray. The findings from the simulations carried out were then compared with the results of the experiment conducted by engineers and researchers in the selected journal.